Computational and Biological Evaluation of β-Adrenoreceptor Blockers as Promising Bacterial Anti-Virulence Agents - Ahmad J. Almalki; Tarek S. Ibrahim; Sameh S. Elhady; Wael A. H. Hegazy; Khaled M. Darwish (MDPI AG, 2022)
Bacterial resistance to antibiotics is an increasing public health threat as it has the potential to affect people at any stage of life, as well as veterinary. Various approaches have been proposed to counteract the bacterial resistance development. Tackling bacterial virulence is one of the most promising approaches that confer several merits. The bacterial virulence is mainly regulated by a communication system known as quorum sensing (QS) system. Meanwhile, bacteria can sense the adrenergic hormones and eavesdrops on the host cells to establish their infection, adrenergic hormones were shown to enhance the bacterial virulence. In this study, β-adrenoreceptor blockers were proposed not only to stop bacterial espionage on our cells but also as inhibitors to the bacterial QS systems. In this context, a detailed in silico study has been conducted to evaluate the affinities of twenty-two β-blockers to compete on different structural QS receptors. Among the best docked and thermodynamically stable β-blockers; atenolol, esmolol, and metoprolol were subjected to further in vitro and in vivo investigation to evaluate their anti-QS activities against Chromobacterium violaceum, Pseudomonas aeruginosa and Salmonella typhimurium. The three tested β-blockers decreased the production of QS-controlled C. violaceum, and the formation of biofilm by P. aeruginosa and S. typhimurium. Additionally, the tested β-blockers down-regulated the P. aeruginosa QS-encoding genes and S. typhimurium sensor kinase encoding genes. Furthermore, metoprolol protected mice against P. aeruginosa and S. typhimurium. Conclusively, these investigated β-blockers are promising anti-virulence agents antagonizing adrenergic hormones induced virulence, preventing bacterial espionage, and blocking bacterial QS systems.